Chapter Listy z Warszawy [Letters from Warsaw] by Tytus Czyżewski – an outline of the issues discussed - Geron, Małgorzata (Wydawnictwo Uniwersytetu Łódzkiego, 2025)
In addition to being a painter and poet, Tytus Czyżewski was also an art critic, collaborating with numerous periodicals. Between 1932 and 1937, he published in the “Głos Plastyków” a series of monthly columns that were collectively titled Listy z Warszawy [Letters from Warsaw]. The texts constituted a personal chronicle of Warsaw’s artistic life. The author chronologically commented on the level of contemporary art criticism, which, in his opinion, was characterized by conservatism and lack of openness to new trends in art, which, according to the author, were reaching Poland with a considerable delay. In addition, he shared his comments on the exhibition policy of Towarzystwo Zachęty Sztuk Pięknych, Instytut Propagandy Sztuki, and the National Museum in Warsaw. Czyżewski’s articles reveal the genuineness of observation and a solid evaluative attitude; their concept and the title itself bring to mind his Listy z Paryża [Letters from Paris]. The latter were published in Zwrotnica in 1922–1923 when Czyżewski resided in Paris and was a foreign correspondent collaborating with the magazine.